Alt det der med vagina dentata kan man godt putte skrådt op - Interview med Henning Bech og Vivi Hollænder - Bjerre, Henrik Jøker; Jacobsen, Stefan Gaarsmand; Peters, Rikke Alberg (Slagmark - Tidsskrift for idéhistorie, 2018)
Sexual norms are not universal. Today’s cultural and social norms regarding sexuality consist of many different attitudes, beliefs, desires and practices. This interview with two of the leading Danish experts in sexological studies and sexology discusses sexual norms and practices, sexual discourse, moralism and taboos in current Danish society.